Evaluation of surface phenomena of magnetic biomass for dye removal via surface modeling. Issue 5 (October 2021) - Lingamdinne, Lakshmi Prasanna; Karri, Rama Rao; Khan, Mohammad Rizwan; Chang, Yoon-Young; Koduru, Janardhan Reddy
Abstract: Methylene blue (MB) dye is used in various industries; however, it is detrimental to both humans and the environment. This study reports on the adsorptive removal of methylene blue (MB) using a magnetically modified agro-waste: iron oxide loaded Lonicera japonica flower powder (IOLJF). The interaction effects of operating variables such as the initial MB concentration, temperature, dosage of IOLJF, and pH on the IOLJF removal efficiency for MB were investigated systematically and statistically. The results showed that the adsorptive removal of MB was explained well by the pseudo-second-order (PSO) kinetic model and the Langmuir and Freundlich isotherms. The maximum uptake capacity was 403.44 mg/g at pH 6.0 and 293 K. The MB adsorption process was complex on the surface of the IOLJF. To comprehend the essential characteristics and envision the removal efficiency in the batch adsorption process, two approaches were used, namely the response surface methodology (RSM) and the data-driven adaptive neuro-fuzzy inference system (ANFIS). The RSM (R 2 = 0.9782) and ANFIS (R 2 = 0.9964) model predictions were both good and comparable with the experimental data. Further, it was found that the magnetic biomass could be re-used for up to seven cycles without losing its efficacy of 95%. Overall, the results indicated that the IOLJF had sufficient potential for wastewater treatment. Graphical Abstract: ga1 Highlights: Feasibly synthesized iron oxide impregnated Lonicera japonica flower powder (IOLJF). Optimization of process variables for maximum removal of MB by RSM. The influence of process parameters on the adsorption process along with interaction effects was studied systematically. A data-driven adaptive neuro-fuzzy inference system (ANFIS) is implemented. IOLJF showed good efficiency and better adsorption capacity and was re-used for 7 cycles.